bOHOslOv’ja cilisnOHO učnivstva ta jOHO implementacija v sučasnij cerkOvnij spilʹnOti = Theology of Holistic Discipleship in the Contemporary Ecclesial Community - Stankevych, Vitalii (Bogoslovskie razmyšlenija, 2019)
The article considers theological understanding of the New Testament discipleship as a holistic phenomenon. The research is based on the philosophical ideas of А. Macintyre, where he proposes a return to a holistic understanding of the phenomenon through the comprehension of three stages of its history: prosperity, decline, and recovery. As a result of the study of iscipleship theology, an ideal model of discipleship in the New Testament texts was discovered, which was realized in two main models: the discipleship of Jesus and the discipleship of the apostle Paul. The peculiarities of the development, the main tendencies of the New Testament discipleship and its decline in the history of the church were also found out. The steps of restoration of the New Testament discipleship in the modern ecclesiological community are suggested. Recovery is possible due to the integration of all modern practices into a holistic phenomenon in the context of a particular ecclesiological community. The relationship of the teacher and the disciple in Christ is the core of discipleship, discipleship is the core of the church, which indicates the relevance of discipleship in the context of understanding the ontology of ecclesia.